EXAMINING NEUROLOGICAL COMPLICATIONS IN PAEDIATRIC MOYAMOYA DISEASE PATIENTS FOLLOWING GENERAL ANAESTHESIA, PATNA: A RETROSPECTIVE COHORT ANALYSIS. - Kumar, Sanjay (Student's Journal of Health Research Africa, 2024)
Background Moyamoya disease (MMD) is a rare cerebrovascular disorder characterized by arterial narrowing, particularly affecting paediatric populations. General anaesthesia in paediatric MMD patients presents challenges due to the risk of neurological complications. This study investigates the incidence and factors associated with neurological complications in paediatric MMD patients undergoing general anaesthesia. Methods A retrospective analysis was carried out on 130 paediatric MMD patients who underwent general anaesthesia. Demographic characteristics, preoperative status, surgical procedures, anaesthetic management, intraoperative events, and postoperative neurological complications were analyzed. Statistical tests (logistic regression analysis or chi-square testing), were used to identify correlation between variables using SPSS version 20.0. Results The cohort had a mean age of 8.5 years, with 85% presenting ischemic symptoms. Revascularization procedures were predominant (90%), with 15% encountering intraoperative complications. Postoperatively, 20% experienced neurological complications, most commonly transient ischemic attacks (10%). Significant associations were found between intraoperative hemodynamic instability and prolonged surgical duration with a raised risk of postoperative neurological complications. Conclusion Paediatric patients with MMD undergoing general anaesthesia are at risk of neurological complications, particularly with prolonged surgeries and intraoperative hemodynamic instability. Optimal perioperative management strategies are essential to mitigate these risks and improve patient outcomes. Recommendations Multidisciplinary collaboration, meticulous intraoperative monitoring, and tailored anaesthetic management are recommended to optimize outcomes in paediatric MMD patients undergoing general anaesthesia.